Microbial Life in Arid Environments: Prospects and Achievements - Sasson, A (Annals of Arid Zone, 2016)
Soil microorganism are only part of the eco-system and recent work has shown that results obtained in soil microbiology were in many respects cognate to those obtained in phytoecology. Problems related to the microbiology of arid arid semi-arid soils must he tackled from ecological and physiological viewpoints with consequently less descriptive studies. This is nevertheless necessary when one deals with environments, such as arid and desert areas, which have received little attention from microbiologist. It is obvious that for countries where an old scientific tradition allowed for accumulation of data on microbial biocenoser, a switch to other aspects of microbiology in necessary. One might therefore write with Alexander 11964) that "the pvhsiological basis of microbial distribution, the geochemical functions of the population, the biochemical relationships between species and communities, the phenotypic and genotypic modifications of microorganism in response to environmental changes and population pressure, the ecological and biochemical significance of the primary ecological determinants and the metabolic basis for dominance of individual genera in specific ecosystems are but a few of the problems awaiting careful and perceptive inquiry by experimental rather than descriptive approaches and by means of in vivo rather than in vitro view of microbial biochemistry and ecology".